2017
DOI: 10.1053/j.gastro.2016.12.019
|View full text |Cite
|
Sign up to set email alerts
|

In Patients With Severe Alcoholic Hepatitis, Prednisolone Increases Susceptibility to Infection and Infection-Related Mortality, and Is Associated With High Circulating Levels of Bacterial DNA

Abstract: Patients with SAH given prednisolone are at greater risk for developing serious infections and infections after treatment than patients not given prednisolone, which may offset its therapeutic benefit. Level of circulating bDNA before treatment could identify patients at high risk of infection if given prednisolone; these data could be used to select therapies for patients with SAH. EudraCT no: 2009-013897-42; Current Controlled Trials no: ISRCTN88782125.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
180
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(185 citation statements)
references
References 24 publications
(38 reference statements)
1
180
1
1
Order By: Relevance
“…Infections are common in severe AH with 12%‐26% prevalence at the time of admission, with up to half infected at some point while receiving corticosteroids . Infection‐related biomarkers like pretreatment serum lipopolysaccharide, bacterial DNA, high‐sensitivity C‐reactive protein, and procalcitonin are associated with the risk of infection and 90‐day mortality . Furthermore, as mentioned previously, the presence of SIRS at admission, with or without infection, predicts multiorgan failure (especially AKI) and early death .…”
Section: Diagnosis and Treatment Of Alcohol‐associated Liver Diseasesmentioning
confidence: 85%
See 1 more Smart Citation
“…Infections are common in severe AH with 12%‐26% prevalence at the time of admission, with up to half infected at some point while receiving corticosteroids . Infection‐related biomarkers like pretreatment serum lipopolysaccharide, bacterial DNA, high‐sensitivity C‐reactive protein, and procalcitonin are associated with the risk of infection and 90‐day mortality . Furthermore, as mentioned previously, the presence of SIRS at admission, with or without infection, predicts multiorgan failure (especially AKI) and early death .…”
Section: Diagnosis and Treatment Of Alcohol‐associated Liver Diseasesmentioning
confidence: 85%
“…If infection is present, appropriate antibiotics should be started immediately. Although there have been reports of frequent fungal infections resulting in high mortality, particularly Aspergillus species, in corticosteroid‐treated patients with AH in France and Belgium, this has not been reported elsewhere in Europe or the United States . Despite these concerns, the presence of infection alone has not been shown to be a driver of short‐term mortality .…”
Section: Diagnosis and Treatment Of Alcohol‐associated Liver Diseasesmentioning
confidence: 99%
“…Recent studies have indicated that AH results in systemic inflammation that affects multiple organ systems. 3941 Tissue damage from systemic inflammation associated with AH is another possible and likely source of K18 release. While measurements of LDH and AST, which are widely expressed, did not correlate with M30 or M65, it remains a possibility that cell death in non-hepatic tissues are potential additional sources of M30 and M65 release.…”
Section: Discussionmentioning
confidence: 99%
“…Although most of the studies investigating the gut–liver axis focus on bacteria and bacterial products, little is known about another integral component of the gut microbiota, the commensal fungi in the gut (also called mycobiota). Invasive fungal infections, primarily with Candida albicans and Aspergillus , occur in patients with alcoholic hepatitis and are associated with a high mortality …”
mentioning
confidence: 99%